2018
DOI: 10.5430/irhe.v3n2p35
|View full text |Cite
|
Sign up to set email alerts
|

Mental Toughness in Collegiate Strength and Conditioning: Widely Used, Widely Misunderstood

Abstract: Researchers explored the value of mental toughness (MT) for strength and conditioning coaches (SCC) for women's basketball of a NCAA Division I conference. Eight SCCs completed a questionnaire and six participated in a semi-structured interview. Results showed that, while there is no agreement whether MT can be developed in student-athletes or about its key attributes, all coaches believe MT is of value. Further, none of the participants reported being aware of or using an instrument to measure MT. Conclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 8 publications
5
6
0
1
Order By: Relevance
“…MSCCs also indicated that MT can affect optimal performance by more than 61 percentage points and there was consensus that there was value in MT training. Similar views have been identified in prior MT research with SCCs (Stamatis et al, 2018), supporting the need for continued investigation dedicated to identifying approaches to train MT. Although MSCCs utilized MT training less than they desired, they did report incorporating MT training into their athletic training protocols.…”
Section: Trainingsupporting
confidence: 71%
See 3 more Smart Citations
“…MSCCs also indicated that MT can affect optimal performance by more than 61 percentage points and there was consensus that there was value in MT training. Similar views have been identified in prior MT research with SCCs (Stamatis et al, 2018), supporting the need for continued investigation dedicated to identifying approaches to train MT. Although MSCCs utilized MT training less than they desired, they did report incorporating MT training into their athletic training protocols.…”
Section: Trainingsupporting
confidence: 71%
“…characteristics of mentally tough athletes, features that represent a lack of MT), the coaches had little confidence in their understanding of MT, and there was high variability in the responses of many of the Phase 1 items that addressed the definition/characteristics of MT. Taken together, these findings demonstrate the conceptual imprecision that has been an ongoing issue in the MT literature in sport both in general (see Gucciardi & Hanton, 2016) and in the MT research involving US coaches (Wall et al, 2020) and US collegiate strength coaches (Stamatis et al, 2018).…”
Section: Conceptualizationsupporting
confidence: 52%
See 2 more Smart Citations
“…Es debido a la disparidad y confusión en la operatividad de la MT la importancia de crear y mantener temas tanto en investigación (Weinberg, Freysinger & Mellano, 2018), como en la práctica (Stamatis, Robinson & Morgan, 2018) y no solo en la abundancia de definiciones 1 (Clough, Earle & Sewell, 2002;Gucciardi, Gordon & Dimmock, 2008;Jones, Hanton & Connaughton, 2002), pero sí en inventarios y/o cuestionarios, lo cual es una indicación de las aún existentes discrepancias de asuntos cruciales en la comunidad científica, tales como, si un modelo Uni -o Multidimensional debiera ser adoptado para conceptualizar la MT basándose en las propiedades psicométricas de varios de esos instrumentos, en donde los resultados del análisis del estudio de la confiabilidad de la MT y de la viabilidad de sus conclusiones aún se encuentran en proceso (Gucciardi, 2017(Gucciardi, , 2018.…”
Section: Introductionunclassified